Syringocystadenocarcinoma Papilliferum in a Fifteen-Year-Old Girl: A Case Report and Review of the Literature - Jordan N. Halsey; Esteban Fernandez Faith; Suzanna J. Logan; Archana Shenoy; Kathleen M. Schieffer; Catherine E. Cottrell; Anna P. Lillis; Jennifer H. Aldrink; Bhuvana A. Setty; Gregory D. Pearson (Case Reports in Dermatological Medicine)
Syringocystadenocarcinoma papilliferum (SCACP) is a rare malignant neoplasm arising from adnexal tissues and is the malignant complement to the benign neoplasm syringocystadenoma papilliferum (SCAP). SCACP lesions appear as raised nodules or inflammatory plaques and can be associated with SCAP or nevus sebaceous. There have been fewer than 100 described cases of this neoplasm in the literature, and all previously published cases have been described in adults, with the majority occurring in the elderly. We present a case of an adolescent female with a syringocystadenocarcinoma papilliferum arising from a large thigh mass harboring an in-frame alteration in MAP2K1 along with a brief review of the literature.